Engorde de cangrejo rojo ucides occidentalis en corrales a diferentes densidades - Escobar Astudillo, Oscar Rolando (2008)
The present work one carries out in the island Costa Rica, belonging to the canton Santa. Rosa, county The Gold. You uses twelve corrals of eight m2, in a rectangular way. These were built with mesh and mangrove stakes and covered the whole superior contour of the corral with zinc. The density of three crab / m2 was significantly better than the other densities that had five, seven nine crabs / m2 respectively. The weight was statistically better in the Treatment One that corresponds three crabs / m2. In the final weight I am better in the treatment one that corresponds three crabs / m2. The final height is better the treatment four that corresponds nine crabs / m2. In the final width the treatment one went better than it corresponds three crabs / m2. The survival was of ninety three% and a mortality seven% of a total of five hundred seventy six sowed crabs. The salinity that was sowed went from twenty-eight ppt to the beginning of the investigation and after six months of cultivation the reading stayed in trenita ppt, for the rising thing it is a species that presents an easy adaptability and development in these cultivation types. The Cost of production of the crab is of twenty-three cents of dollar. The gross entrance for each crab is of twenty seven cents of dollar. Of each dollar invested in the upbringing of the crab a benefit it is obtained of $2,16. The utility that is perceived by the upbringing of the crabs in the lapse of six months is of $144.